Ізольована дисекція верхньої брижової артерії: ендоваскулярне лікування. Клінічний випадок - S. M. Furkalo; Yu. H. Vahis; A. O. Danylets (Ukrainian Heart Journal, 2026)
The aim – to describe a case of elective endovascular treatment of asymptomatic spontaneous isolated dissection of the superior mesenteric artery with a self-expanding covered stent via right transbrachial access and to justify the indication for intervention based on morphological risk criteria.Materials and methods. The follow-up of a 67-year-old man with coronary artery disease, compensated type 2 diabetes mellitus, arterial hypertension, dyslipidaemia and previous left total hip arthroplasty is presented. The dissection was found incidentally at screening computed tomography angiography during an annual cardiovascular evaluation. The patient was asymptomatic. Imaging showed a patent false lumen 1.8 cm in diameter with compression of the true lumen and no re-entry (Yun type IIb). The decision to intervene was made by a multidisciplinary team taking into account the morphology, false lumen size and a comorbidity profile that reduced tolerance both to potential acute mesenteric decompensation and to open revascularization.Results. A self-expanding covered stent was implanted into the proximal segment of the superior mesenteric artery via right transbrachial access. The access was selected due to a favourable cannulation angle, the presence of the hip prosthesis, and reduced risk of haemorrhagic complications during dual antiplatelet therapy. Restoration of the true lumen, exclusion of the false lumen and preservation of the main side branches were achieved. The patient was discharged on the first postoperative day in a stable condition.Conclusions. In carefully selected patients with asymptomatic dissection and morphological risk markers, single-stage covered stent repair via transbrachial access may be justified. Given the absence of randomized data, morphological criteria should be regarded as a possible additional argument for intervention in selected patients rather than a universal threshold.